Psychological Factors on Student Learning Outcomes - Ari Suningsih; Diyana Dewi (Basic and Applied Education Research Journal, 2020)
This study aims to determine the effect of psychological factors on the incompleteness of student learning outcomes. The type of this research is quantitative with five independent variables and one dependent variable. The population in this study were all students of MTs Negeri 1 Pringsewu, with a sample of students of class VIII.B totaling 30 respondents. Sampling is done by random sampling technique. Furthermore, to obtain psychological factor data, a questionnaire was used, and data on students' learning outcomes was obtained through documentation of student learning test results. Based on the results of data analysis with the multiple regression test, it was concluded that psychological factors influence the incompleteness of student learning outcomes with a contribution of 47%.